Schädigungs- und Versagensverhalten hochfester Leichtbauwerkstoffe unter Biegebeanspruchung - Tsoupis, Ioannis (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2017)
A general methodology for the simulation-based determination of damage and failure under bending load for materials with high lightweight potential was developed within this work. In this context, a fundamental understanding about the damage and failure mechanisms during bending sharp radii was simultaneously created both in experimental and simulation-based studies. The developed methodology and the acquired knowledge make a device contribution to design bending dominated forming operations economically, accurately and reliably in practice as well as to predict and prevent the probability of damage and failure prior to manufacture and production in the futur